1964
DOI: 10.1161/01.cir.30.6.865
|View full text |Cite
|
Sign up to set email alerts
|

The Frank Vectorcardiogram in Mitral Stenosis

Abstract: The vectorcardiographic findings in 29 patients with mitral stenosis are presented. Five patients had normal QRS loops, and five had classical loops of right ventricular hypertrophy with predominant anterior forces. The remaining 19 patients had posteriorly oriented loops with normal rotation. The characteristics of these latter loops were analyzed in detail and compared with the findings in series of normal subjects. The midportions of the horizontal plane QRS loops were found to be signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1966
1966
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Although a number of studies have been made in mitral stenosis, the investigators have used the 12-lead electrocardiogram22-25 or the cube system,2629 and until recently there have been very few using the orthogonal lead systems. Taymor et al 30 reported the results of their vectorcardiographic studies in mitral stenosis using the Frank system. Their findings were similar to the data obtained in group I of our series.…”
Section: Discussionmentioning
confidence: 99%
“…Although a number of studies have been made in mitral stenosis, the investigators have used the 12-lead electrocardiogram22-25 or the cube system,2629 and until recently there have been very few using the orthogonal lead systems. Taymor et al 30 reported the results of their vectorcardiographic studies in mitral stenosis using the Frank system. Their findings were similar to the data obtained in group I of our series.…”
Section: Discussionmentioning
confidence: 99%